A study on the heave performance and loads of the critical connections of a novel dry tree semisubmersible concept using numerical and experimental methods. (15th September 2016) - Jiang, Zhe; Xie, Bin; Cui, Weicheng; Du, Qinggui; Tian, Xinliang
Abstract: Deepwater tumbler platform (DTP) is a novel semisubmersible concept in offshore industry, which utilizes double tier pontoons to improve heave performance so as to support dry tree systems, and to enable the platform stable unconditionally by installing ballast in lower tier pontoons (LTPs). However, the effectiveness of double tier pontoons on reducing heave motions has not been extensively studied, and additionally, the weight of LTPs brings in extra structural loads on the connections between the upper tier pontoons and LTPs, which make this connection the most critical one in the design of DTP. Therefore, the heave performance and the loads of the connections are the two main concerns in developing the DTP concept. In this paper, the hydrodynamic behavior of DTP and the loads of the connections are analyzed by numerical simulations as well as model tests. Good agreement of the numerical results with the experimental measurements was found and the results of both prove that the design of double tier pontoons greatly improves the heave performance. Besides, considerable amount of forces and bending moments by the motions of LTP were exerted on the connections. Finally, through a sensitivity study on the LTP depth, the relationship among LTP depth, heave performance and connection loads were discovered. This study illustrates the use of double tier pontoons in improving heave performance and provides important design guidance on the DTP design. Highlights: Numerical analysis and model tests were conducted on a novel dry tree semi concept. Effect of double tier pontoons on reducing heave motion and loads was studied. The larger the elevation of LTPs, the larger for local loads and smaller for heave.